PENGARUH TEKANAN WAKTU DAN SKEPTISISM PROFESIONALTERHADAP DETEKSI FRAUD (Studi Kasus Pada Kantor Akuntan Publik di Kota Surakarta dan Yogyakarta) - de Jesus Ximenes, Maria Angelina Antonio Modesta; Rispantyo, Rispantyo; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
The purpose of this study is to analyze the effect of time pressure on frauddetection, profesional skepticism towards fraud detection. This study uses primarydata from answers to questionnaires distributed to all auditors in the cities ofSurakarta and Yogyakarta. The Sampling technique uses the Probability Samplingmethod with random Sampling Samples. The results of this study simultaneouslyvariable time pressure and professional skepticism have significant effect on frauddetection while the professional skepticism factor has a positive and significanteffect on fraud detection.